(untitled) (KULT_online, 2014)
Life Writing and Political Memoir – Lebenszeugnisse und Politische Memoiren aims at analyzing political memoirs from the 19th and 20th centuries. How is it that they both shape and are shaped by historical and media discourses? This interdisciplinary volume provides ten case studies of life writing produced by political actors through the light of a post-modernist approach. The authors identify the discursive points of contradiction that reveal the artificiality and non-factuality of such cultural products. By doing so, this edited volume sheds light not only on past methodological shortages in history research but also on the conscious or unconscious motivations of political memoir writers discursively constructing a certain identity.